Respuesta :
Answer:
-6
Step-by-step explanation:
You want to subtract the 2x from both sides, leaving you with x+5= -1 and then you want to subtract the 5 from both sides which gets you to your final answer of x= -6
Answer:
x = -6
General Formulas and Concepts:
Pre-Alg
- Order of Operations: BPEMDAS
Algebra I
- Equality Properties
Step-by-step explanation:
Step 1: Define equation
3x + 5 = 2x - 1
Step 2: Solve for x
- Subtract 2x on both sides: x + 5 = -1
- Subtract 5 on both sides: x = -6
Step 3: Check
Plug in x to verify it's a solution.
- Substitute: 3(-6) + 5 = 2(-6) - 1
- Multiply: -18 + 5 = -12 - 1
- Add/Subtract: -13 = -13